Pharmacotherapy of mood disorders and psychosis in pre- and post-natal women. (2nd November 2017) - Smith, Beth; Dubovsky, Steven L.
ABSTRACT: Introduction : Untreated mood and psychotic disorders can have substantial adverse impacts on the patient, the fetus and the family, while treatment can ameliorate such problems. To address concerns by clinicians about the risks of psychotropic medications, this review addresses the risk/benefit analysis of somatic therapies for psychiatric disorders during pregnancy and lactation. Areas covered : All available research was reviewed on the impact on pregnancy and breastfeeding of mood and psychotic disorders, and of antidepressants, mood stabilizers, antipsychotic drugs, and electroconvulsive therapy. References cited in other reviews, case series, formal studies, pharmacologic discussions, and theoretical pieces were added. Available case control and other studies were critically reviewed and diverse explanations for their findings were considered. Expert opinion : The potential benefits of treatment of mood and psychotic disorders often outweigh the risks after alternative therapies have been considered. Some medications, particularly paroxetine and valproate, pose greater risks during pregnancy, while the teratogenic risks of lithium have probably been overstated. There is more experience with first than with second generation antipsychotic drugs during pregnancy and lactation. Nursing an infant is possible while taking a number of antidepressants, mood stabilizers or antipsychotic drugs.